Treatment efficacy of anti-hypertensive drugs in monotherapy or combination: ATOM systematic review and meta-analysis of randomized clinical trials according to PRISMA statement. Issue 30 (July 2016) - Paz, Marco A.; de-La-Sierra, Alejandro; Sáez, Marc; Barceló, María Antonia; Rodríguez, Juan José; Castro, Sonia; Lagarón, Cristina; Garrido, Josep M; Vera, Pilar; Coll-de-Tuero, Gabriel
Abstract: Background: The relative efficacy of antihypertensive drugs/combinations is not well known. Identifying the most effective ones and the patients' characteristics associated with best performance of the drugs will improve management of hypertensive patients. Objective: To assess the blood pressure (BP) reduction attributed to antihypertensive drugs and identify characteristics associated with BP decrease. Data sources: MEDLINE, Cochrane Central Register of Controlled Trials from inception through July 2012 and selected papers. Study eligibility criteria: Double-blind, randomized clinical trials whose main result was the reduction in BP by antihypertensive treatment, with study population ≥50 or ≥25 if the study was a crossover, follow-up of at least 8 weeks, and available required data. Study appraisal and synthesis methods: Study data were independently extracted by multiple observers and introduced in an electronic database. Inconsistencies were resolved by discussion and referral back to the original articles. Meta-analysis was performed according to PRISMA statement and using a Bayesian framework. Main Outcome(s) and Measure(s): Mean decrease in systolic (SBP) and diastolic blood pressure (DBP) achieved by each drug or combination. Results: Two hundred eight trials including 94, 305 patients were identified. In monotherapy, most drugs achieved 10 to 15 mm Hg SBP and 8 to 10 mm Hg DBP decreases. Olmesartan/amlodipine, olmesartan/hydrochlorothiazide, felodipine/metoprolol, and valsartan/hydrochlorothiazide were the combinations leading to the greatest mean SBP reductions (>20 mm Hg). Female sex and body mass index >25 kg/m 2 were associated with more pronounced SBP and DBP reductions, whereas Afro-American ethnicity was associated with BP reductions smaller than the median. Results were adjusted by study duration, cardiovascular disease, and diabetes mellitus. Still, the estimation was performed using the mean administered doses, which do not exactly match those of the available drug formats. Limitations: Data corresponded to those obtained in each of the included trials; the analysis of the combinations was limited to the most recent ones; estimations were performed using the mean administered doses. Conclusions and implications: Certain drug combinations achieve BP reductions ranging from 20 to 25/10 to 15 mm Hg. Sex, ethnicity, and obesity are associated with antihypertensive response. This information can contribute to better selection of the antihypertensive drug, depending on the magnitude of pretreatment BP elevation. Guidelines should be revised. Abstract : Supplemental Digital Content is available in the text